2003
DOI: 10.1034/j.1600-0560.2003.300102.x
|View full text |Cite
|
Sign up to set email alerts
|

p63 expression in normal human epidermis and epidermal appendages and their tumors

Abstract: p63 expression may be a marker of basal/progenitor cells in tumors of epidermis and epidermal appendages, and may be a diagnostic marker of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
85
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 27 publications
20
85
0
4
Order By: Relevance
“…Kaufmann et al The expression of p63 in normal human epidermis, cutaneous appendages and skin carcinomas has been recently assessed. [16][17][18] p63 seems to play a major role in ectodermal development, in the maintenance of the basal cell population of stratified epithelia, and also in the terminal differentiation of epithelia. [6][7][8] In vitro studies, using transformed human keratinocytes, have shown that p63 is a nuclear transcription factor that triggers keratinocyte differentiation and is downregulated in terminally differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaufmann et al The expression of p63 in normal human epidermis, cutaneous appendages and skin carcinomas has been recently assessed. [16][17][18] p63 seems to play a major role in ectodermal development, in the maintenance of the basal cell population of stratified epithelia, and also in the terminal differentiation of epithelia. [6][7][8] In vitro studies, using transformed human keratinocytes, have shown that p63 is a nuclear transcription factor that triggers keratinocyte differentiation and is downregulated in terminally differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,14 The expression of p63 in normal human epidermis, cutaneous appendages and skin carcinomas has been recently assessed. 16,17 In these studies, p63 was detected in the epidermal and adnexal basal/ myoepithelial cells and it has been suggested that p63 might be used as a diagnostic marker for epidermal or adnexal tumors in the skin. [16][17][18] Cutaneous metastases may be the initial manifestation of some neoplasms, including adenocarcinomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…p63 is a diagnostic marker of basal/progenitor cells of the adnexal tumors. p63 might block the apoptosis inducing activity of p53 and thus could maintain the proliferative capacity of basal/progenitor cells 15,16 . P63 expression was also reported in trichilemmal carcinoma 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Possui também importante papel no desenvolvimento e na proliferação epitelial de diversas estruturas, como, as crânio-faciais (TSUJITA-KYUTOKU et al, 2003).…”
Section: Ahomadegbe 2003)unclassified